2015
DOI: 10.1128/aem.02878-14
|View full text |Cite
|
Sign up to set email alerts
|

A Novel DNA-Binding Protein, PhaR, Plays a Central Role in the Regulation of Polyhydroxyalkanoate Accumulation and Granule Formation in the Haloarchaeon Haloferax mediterranei

Abstract: c Polyhydroxyalkanoates (PHAs) are synthesized and assembled as PHA granules that undergo well-regulated formation in many microorganisms. However, this regulation remains unclear in haloarchaea. In this study, we identified a PHA granule-associated regulator (PhaR) that negatively regulates the expression of both its own gene and the granule structural gene phaP in the same operon (phaRP) in Haloferax mediterranei. Chromatin immunoprecipitation-quantitative PCR (ChIP-qPCR) assays demonstrated a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…This mechanism is analogous to the one proposed by Prieto et al for the regulation of the PHA biosynthesis genes in Pseudomonas oleovorans (currently known as P. putida) by phasin PhaF Pp (10). PhaR was also found in H. mediterranei, but the regulation pattern of phaP by PhaR in this archaeon is slightly different from that of its bacterial counterparts, as it was shown to repress the expression of both its own gene and phaP, which are transcribed from the same operon (phaRP) (36).…”
Section: Role Of Phasins In Pha Metabolismmentioning
confidence: 99%
“…This mechanism is analogous to the one proposed by Prieto et al for the regulation of the PHA biosynthesis genes in Pseudomonas oleovorans (currently known as P. putida) by phasin PhaF Pp (10). PhaR was also found in H. mediterranei, but the regulation pattern of phaP by PhaR in this archaeon is slightly different from that of its bacterial counterparts, as it was shown to repress the expression of both its own gene and phaP, which are transcribed from the same operon (phaRP) (36).…”
Section: Role Of Phasins In Pha Metabolismmentioning
confidence: 99%
“…This result confirmed that Gly 16 , Ser 47 , and Asp 195 are indeed essential for nPHA granule hydrolysis. Ser 47 in the classical lipase box (G-X-S-X-G) may be the active-site serine (6,38,39) (18,21,22). However, no putative PHA depolymerase was found in this PHA granule proteome.…”
Section: Resultsmentioning
confidence: 87%
“…To further biochemically determine the hydrolysis activity of PhaZh1 with the nPHA granules, we expressed PhaZh1 with a C-terminal His 6 tag (His 6 -PhaZh1) in the haloarchaeon H. volcanii H1424 (26). The promoter of the expression plasmid pTA1228 (27) used in this study was replaced with a strong constitutive promoter of P.phaR in which its negative cis element has been deleted (22). The PHA depolymerase activity of His 6 -PhaZh1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations